Komunikasi Krisis Polri: Strategi Image Repair Polri Dalam Tragedi Kanjuruhan - Yogie Alwaton (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
This study aims to analyze Polri's image repair strategy in the Kanjuruhan Tragedy. Many parties regretted this incident, so that there was a mutual shift of responsibility, including the assumption that the police were deemed guilty for violating FIFA rules regarding tear gas shooting. Of course, as a result of this incident the image of the police is at stake and image restoration is needed. By using the qualitative content analysis method through texts published by Kompas.com for the period 1 October - 1 November 2022, it was found that the Polri focused on restoring image by using many strategies such as simple denial, provocation, defeasibility, good intention, bolstering, compensation and corrective actions. However, the results also show that there is inconsistency and neglect of the apology or mortification strategy by the National Police. In fact, this strategy is needed when an organization is hit by a crisis.